2022
DOI: 10.1111/itor.13164
|View full text |Cite
|
Sign up to set email alerts
|

On the role of metaheuristic optimization in bioinformatics

Abstract: Metaheuristic algorithms are employed to solve complex and large-scale optimization problems in many different fields, from transportation and smart cities to finance. This paper discusses how metaheuristic algorithms are being applied to solve different optimization problems in the area of bioinformatics. While the text provides references to many optimization problems in the area, it focuses on those that have attracted more interest from the optimization community. Among the problems analyzed, the paper dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 219 publications
0
5
0
Order By: Relevance
“…In the subsequent step, which involves modifying the initial population, fundamental operators are utilized for successive generations, aiming to reach the global optimum [29]. Given the random initiation in the evolutionary technique for Multiple Sequence Alignment (MSA), the Evolutionary Algorithm for Sequences (EAS) has taken additional steps to enhance similarities in sequence alignment [9]. Evolutionary computation provides intriguing approaches for multisequence alignment [21], resulting in higher alignment accuracy during the MSA runtime process.…”
Section: Evolutionary Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the subsequent step, which involves modifying the initial population, fundamental operators are utilized for successive generations, aiming to reach the global optimum [29]. Given the random initiation in the evolutionary technique for Multiple Sequence Alignment (MSA), the Evolutionary Algorithm for Sequences (EAS) has taken additional steps to enhance similarities in sequence alignment [9]. Evolutionary computation provides intriguing approaches for multisequence alignment [21], resulting in higher alignment accuracy during the MSA runtime process.…”
Section: Evolutionary Methodsmentioning
confidence: 99%
“…These algorithms mimic natural processes or use population-based strategies, which help them find optimal solutions and avoid becoming stuck in local optima. Due to their adaptability and flexibility, these algorithms are well-suited for addressing the challenges and complexities of the MSA problem [9].…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatics is an interdisciplinary field that combines biology, computer science, and statistics to analyze and interpret biological behaviour [ 1 ]. It identifies and diagnoses cancer by examining gene activity and cellular function.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the effectiveness of optimization and heuristic methods such as Bayesian optimizer, grid search, and random search methods in improving model prediction. Calvet et al [ 23 ] demonstrated the effect of optimization algorithms in solving bioinformatics problems such as molecular docking and protein structure prediction. They suggested the combination of multiple heuristic and optimization algorithms to solve modern computational problems.…”
Section: Introductionmentioning
confidence: 99%